Improved‐efficiency quasi‐two‐stage current‐source‐mode SIMO LED driver. Issue 12 (16th September 2019) - Dong, Zheng; Li, Xiaolu Lucia; Tse, Chi Kong
Abstract : Single‐inductor–multiple‐output (SIMO) light‐emitting‐diode (LED) drivers are attractive, practical solutions for lighting applications. An SIMO LED driver is usually constructed with conventional voltage‐source‐mode dc–dc converters. Current‐source‐mode (CSM) converters, though being highly suited for current driving, are less studied. Simple control, low cost and independent dimming function are among the advantages of CSM SIMO converters. The limiting factors of CSM SIMO converters, however, include the relatively low efficiency and the restricted number of outputs under low‐frequency pulse‐width modulation (PWM) dimming control. In this study, an adaptive current bus technique to the CSM SIMO converter is applied. Results show that a significant improvement in efficiency can be achieved. The low‐frequency PWM dimming method is also analysed and redesigned. Also, we compare the voltage stress in the CSM SIMO converter with traditional input‐series‐connected structure. Results show that the CSM SIMO converter achieves a high‐voltage step‐down ratio without the use of transformers. This study presents detailed analysis and experimental results of the CSM SIMO converter with adaptive current bus.